(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Hanging remains to be one of the common methods of committing suicide. Homicidal and accidental hanging is rare1, 2 . Hence all cases of hanging are considered suicidal until the contrary is proved3.Because of the above, postmortem suspension of the body may be resorted to cloak a crime. Therefore meticulous dissection and sharp distinction between ante mortem hanging and postmortem suspension is warranted.